Emerging Powers, Emerging Markets, Emerging Societies Global Responses - Christensen, Steen Fryba; Xing, Li.; SpringerLink (Online service) (London : Palgrave Macmillan UK (Imprint), 2016)
The rise of emerging or new powers has recently become one of the most researched areas in International Relations. While most studies focus on relations between traditional and emerging powers, this edited collection turns the focus 180 degrees and asks how countries outside these two power sets have reacted to the emerging new world order. Are emerging powers creating a united front in a struggle to change the global order, or are they more concerned with national interests? Are we seeing major changes in the global order, or simply an adjustment by the traditional powers to the emergence of new contenders? In order to the answer these questions, the authors take a broad thematic approach in analyzing recent trends in the interplay between states, markets and societies, concentrating in particular on Latin America, Africa, the Middle East and Europe, and on the three major emerging powers: China, India and Brazil.
Keywords: International relations; Economic policy; Political economy; Globalization; Development economics; International Political Economy